Efektivitas penerapan model discovery learning terhadap kemampuan komunikasi matematis siswa kelas VIII - Amelia, Rika; Hendriana, Heris; Amelia, Risma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research was motivated by the low mathematical communication skills of class VIII students. The aim of the research is to analyze the effectiveness of implementing the Discovery Learning model on students' mathematical communication skills, by comparing the experimental class that uses the Discovery Learning model and the control class that uses conventional learning. This research method is quasi-experimental with a pretest-posttest design in two groups (Pretest-Posttest Control Group Design). The research subjects consisted of students from class VIII-A as the control class and VIII-B as the experimental class, each numbering 25 people at SMP Negeri 2 Takokak. The data collection technique uses instruments to test students' mathematical communication skills on the System of Linear Equations in Two Variables (SPLDV). Students' mathematical communication ability tests were given twice at pretest and posttest. Data processing and analysis uses the Microsoft Excel 2021 application and SPSS 25 software. The results of the research show that the effectiveness of students' mathematical communication skills who learn through the Discovery Learning model is better than conventional learning.